PLASMAPHERESIS IN THE TREATMENT OF MYASTHENIA GRAVIS: OUTCOME AND COMPLICATIONS - Abbas, Maryam; Robert, Helen Mary; Mahmood, Asad; Khan, Saleem Ahmed; Naeem, Mohammad Abdul; Ayaz, Muhammad Ahsan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the outcome and complications of plasmapharesis in treatment of myasthenia gravis and factors linked to poor outcome at hematology unit of a tertiary care teaching hospital of Pakistan Study Design: Prospective comparative study. Place and Duration of Study: Pak Emirates Military Hospital/Armed Forces Institute of Pathology, Rawalpindi, from Jan 2018 to Jul 2019. Methodology: A prospective study was conducted on patients of myasthenia gravis presented at our neurology department. All the complications of the procedure were recorded. Outcomes included recovery, shifting to intensive care unit and death. Pearson chi-square was applied to relate the factors with presence of complications or poor outcome. Results: Hypotension 3 (6%) was the commonest complication faced by the patients followed by chest discomfort 2 (4%) during or after the plasmapharesis. Out of 50 patients, 47 (94%) recovered, 8 (16%) had minor complications, 2 (4%) were shifted to the intensive care unit and 1 (2%) died. Long duration of time between onset of symptoms and first session of plasmapharesis had a significant relationship (p-value <0.05) with presence of complications or poor outcome among the patients of myasthenia gravis undergoing plasmapharesis. Conclusion: Plasmapharesis emerged as effective treatment for this immune based neurological disorder with limited side effects. A neurologist should be aware of these common minor and rare major side effects and pay special attention to the patients with generalized myasthenia gravis and those with long duration of time between onset of symptoms and first session of plasmapharesis. Keywords: ,.